Respon Imun Ikan Nila Salin (Oreochromis Niloticus) Terhadap Pakan yang Diperkaya dengan Probiotik Bacillus Subtilis - Rahmi; Arianti, Nining; Khaeriyah, Andi; Yani, Fitri Indah; Sahabuddin (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
Tilapia is a widely favored type of fish because it has thick meat and a delicious taste. The use of probiotics in tilapia maintenance can increase immunity from disease attacks through the addition of probiotics can increase the nutritional content of feed protein and maintain the balance of digestive tract microbes. The study aims to provide feed enriched with Bacillus subtilis probiotics to see parameters in the form of immune responses through blood pictures in tilapia, survival rates, and daily growth rate values. Tilapia seeds (5-7cm) were maintained in maintenance tanks with 5 treatments and 3 repetitions in the form of treatment without additional B. subtilis, addition of B. subtilis 10³ CFU / mL, addition of B. subtilis 105 CFU / mL, addition of B. subtilis 107 CFU / mL, and treatment with the addition of B. subtilis 109 CFU / mL. The results obtained showed that the addition of B. subtilis probiotics to saline tilapia fish feed with a concentration of 107 CFU/mL could increase the number of erythrocytes and was able to increase the survival value, as well as the daily growth rate of saline tilapia fish (O. niloticus) significantly. However, they did not affect the number of fish leukocytes during maintenance.